Evaluasi Manajemen Media Pembelajaran Pada Madrasah Ibtidaiyah - Ahmad Zainuri; Saepuloh Saepuloh (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
This scientific work is presented to obtain or provide insight into the evaluation of learning media management at Madrasah Ibtidaiyah Negeri 1 Palembang. The method used in this scientific work is to review literature that is relevant to the evaluation of learning media management. The results of this study illustrate that the evaluation of learning media management on media can be carried out methodically and systematically. Evaluation is a step that must be taken in evaluating the management of learning media in an educational institution. In this study, evaluation can be said to be very important. Given that this evaluation is to ensure that the teaching materials used are of guaranteed quality and can carry out their functions to achieve real teaching and learning goals. Evaluation of learning media management can be done in several ways, such as (1) overall initial assessment, namely: (a) expert assessment, (b) individual assessment and (c) individual assessment, small evaluation group, and (2) trial field. Not only that, the results of this study illustrate that the teaching materials used must be evaluated at the beginning of use even before being used or used evenly to avoid fatal (serious) vulnerabilities and damage.